Novel internet of things-spectroscopy methods for targeted water pollutants in household point-of-use environments - Syahidah Nurani Zulkifli; Herlina Abdul Rahim; Nurul Adilla Mohd Subha (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
Ensuring water quality remains a paramount concern to prevent adverse health effects on consumers. Water quality monitoring primarily focuses on water utilities and infrastructure, such as treatment plants and reservoirs. More information is needed on the status of water once it enters the consumption phase, particularly at the point-of-use (POU). Therefore, this study aims to provide a scientific understanding of water quality in response to microbial contaminants in Malaysia’s household water system using the non-invasive benchtop near-infrared (NIR)-Raman spectroscopy approach. This study also provided the effects of seasonal variations and stagnation periods on the quality of water supply, corresponding to microbial contaminants. Findings show that almost 20% of the water samples contained Legionella and Salmonella species through the Raman spectral identification technique. The distinct signature peaks (ranging from 400 cm-1 to 1,800 cm-1) indicative of specific bacterial species are identified. However, benchtop Raman spectroscopy has application constraints in real-time water quality monitoring. Hence, acknowledging its limitation, this study proposed a new internet of things (IoT)-based micro-spectrometer as an alternative to rapid and sustainable POUs water quality assessment. Leveraging IoT protocols enhances the reliability and efficiency of identifying microbiological threats in water supply.